Análise de eficiência energética para algumas redes sem fio de curto e de longo alcance - Kakitani, Marcos Tomio (2014)
The energy efficiency analysis for some short-range wireless networks, such as wireless sensor networks, and for some long-range wireless networks, such as cellular networks is performed in this work. For the wireless sensor networks analysis, non-cooperative and cooperative transmission schemes (considering that a return channel is available or not) are employed. Multiple antennas transmission schemes, realistic power consumption models, and a cost model for different system designs are considered for the cellular networks analysis. We consider that the system is under constraints such as a target end-to-end outage probability and a target end-to-throughput. The results show the most efficient transmission schemes and network designs under different system conditions. The future works plans are also detailed.